Farm households that adopt ICT change production decisions: evidence from India - Tirtha Chatterjee (Agricultural Economics Research Review, 2023)
Farm households in India use information and communication technology (ICT) and ICT devices in making production related decisions. I explore the impact of ICT ownership and use on agricultural diversification and commercialization. Households that adopt ICT opt for higher commercialization, diversify towards high-value crops, invest in modern inputs, and hire more agricultural labour. Villages that adopted mobile technology early and households in those villages drove the impact of ICT adoption on farm diversification. The adoption of ICT leads to diversification by improving awareness and by facilitating access to the credit market, social interaction, and mass media.